Standard degrees for tests results to some physical abilities and defense rebound for tall players in basketball school - hanoon, wasan; Abdul Sattar, Muhannad; Sami, Faris (Journal of Physical Education, 2012)
The test considers from important methods and tools when we using the evaluation because it is a basic role in diagnosis & classification & motive & selection &guiding &prediction and the problem was formatted in some questions like ( what is physical variables that tall players needs n the game and effect on the game ? what is the tests that measures these variables also the defense rebound variable and is there a references standard specialized in that ?) , the aims of research represented by knowing to some physical abilities for tall players in basketball school and their tests and putting new tests to measure defense rebound to one player and tow tall players also limiting the standards degrees ( modified un following method ) to results in some physical abilities & defense rebound for research sample .The researchers depend on tall players from all states of Iraq and their number (50) from ( 63) proposers , after getting results and treated it statistically the researchers concluded that they can limits the standards ( standards degrees modified in following method ) for fast strength to left and right legs & explosive power for arms and leg speed & speed endurance , the recommendation was focus on depending these physical variables & defense rebound on continuous evaluation also using these standards as references standards on preliminaries selection to tall players on basketball players and use it from Iraq basketball association for generate on basketball schools